Assessment of the Effectiveness of Vitamin Supplement in Treating Eczema: A Systematic Review and Meta-Analysis. (31st October 2019) - Zhu, Ziyu; Yang, Ziyi; Wang, Chunyi; Liu, Handeng
Abstract : Background . The morbidity of eczema has increased in the recent years, and the methods to prevent or ameliorate its effects are becoming more important. To this end, this research was conducted to determine the effectiveness of vitamin supplements in eczema therapy. Method . Embase, PubMed, and Cochrane Central Register of Clinical Trials were searched. Only randomized controlled trials were included, and we included all quantified eligible data where the SCORing Atopic Dermatitis (SCORAD) Index or Eczema Area and Severity Index (EASI) scores were applied to assess the severity of eczema. Results . Ten studies fulfilled the inclusion criteria, and eight of them were included for quantitative analysis (total: 456 patients). Compared to the controls, the SCORAD index or EASI decreased in the vitamin supplement group (mean difference −5.96, 95% CI: −7.69 to −4.23 for vitamin D3; mean difference −5.72, 95% CI: −11.41 to −0.03 for vitamin E; and mean difference −3.19, 95% CI: −4.27 to −2.10 for vitamin B12). Conclusion . This study suggests that vitamin supplements could be important therapeutics to help manage eczema patients.